2004
DOI: 10.1530/rep.1.00122
|View full text |Cite
|
Sign up to set email alerts
|

Minor involvement of somatic growth in the onset of puberty of Hatano high- and low-avoidance rats

Abstract: The present study was planned to examine the effects of somatic growth on the determination of timing of puberty using Hatano high-and low-avoidance rats (HAAs and LAAs); the rats were genetically selected from Sprague-Dawley (SD) rats for good or poor performance in a two-way active avoidance-learning test. Since these two lines were found to have different characteristics, such as body weight at birth, maternal care and timing of male puberty, the present study characterized female puberty in Hatano rats and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…PCB-126, however, did not affect the timing of puberty at a dose level of 1 µg/kg/day, which reduced the body weights of offspring on PND24. In addition, it has been shown that compensation of somatic growth does not always advance puberty in the rat [17]. Other factors, such as those exerting antiestrogenic effects, may also be involved in the delay of puberty since estradiol-17β, one of the key hormones affecting the onset of puberty in the rat, is antagonized by AhR agonists [11].…”
Section: Discussionmentioning
confidence: 99%
“…PCB-126, however, did not affect the timing of puberty at a dose level of 1 µg/kg/day, which reduced the body weights of offspring on PND24. In addition, it has been shown that compensation of somatic growth does not always advance puberty in the rat [17]. Other factors, such as those exerting antiestrogenic effects, may also be involved in the delay of puberty since estradiol-17β, one of the key hormones affecting the onset of puberty in the rat, is antagonized by AhR agonists [11].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that HAA rats matured earlier in terms of behavioral development [13], and puberty [21,22]. These results suggest that immunological development occurs earlier in HAA than LAA rats as well as behavioral and endocrine developments.…”
Section: Discussionmentioning
confidence: 61%
“…One of the most interesting features resulting from the genetic selection of Hatano rats has been their stress response: HAA rats are generally more reactive to stress than LAA rats [15] with the notable exception of prolactin secretion [3]. In addition, compared to LAA rats, HAA rats show earlier physical, behavioral and sexual maturation [13,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that HAA rats ovulate more oocytes than LAA rats [2,14], and it is well known that follicular development in mammals is controlled by the two pituitary-derived glycoprotein hormones, FSH and LH [15]. During follicular development, most follicles undergo atretic degeneration, whereas a few of them, under stimulation from cyclic gonadotropins, reach the preovulatory stage [16,17].…”
Section: Discussionmentioning
confidence: 99%